Evaluation of the Determinant Factors and Clinical Implications of Self-Care Agency Among Patients with Acute Myocardial Infarction. (February 2021) - Maruta, Megumi; Moriyama, Shiho; Mizuguchi, Yukio; Hashimoto, Sho; Yamada, Takeshi; Taniguchi, Norimasa; Nakajima, Shunsuke; Hata, Tetsuya; Takahashi, Akihiko
In patients with acute myocardial infarction treated with percutaneous coronary intervention (PCI), effective post-hospital care, partially determined by self-care agency, is critical for long-term prognosis. However, the relationship between agency and sociodemographic characteristics requires elucidation. One hundred and six outpatients participated in our study. Self-care agency was assessed with the Self-care Agency Questionnaire (SCAQ). We evaluated its correlation with patients' sociodemographic characteristics and morale on the Ikigai-9 Questionnaire. Mean SCAQ scores were higher in those who were younger, male, living with someone, and more educated compared to their counterparts. Furthermore, SCAQ scores were correlated with Ikigai-9 scores. Multivariate logistic regression analyses indicated that social participation, employment status, and morale were independent predictors of high SCAQ scores. A comprehensive approach utilizing medical professionals, families, and the local community is needed to promote self-care agency in patients receiving primary PCI.